Soluções Tecnológicas para a Mobilidade de Pessoas com Deficiência Visual: Realidade Virtual e Navegação Interna com Wi-Fi - Souza, Ana; Fonseca, Davi; Amorim, Glauco; Santos, Joel dos (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2025: Anais Estendidos do XXXI Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2025.15979, 2025)
This study addresses navigation challenges for visually impaired individuals by developing two complementary solutions. First, a Virtual Reality (VR) training tool with multimodal feedback (audio and tactile) was created to help users develop spatial skills and mental mapping abilities safely, without real-world risks. The VR system supports Orientation and Mobility training techniques. Second, a cost-effective indoor localization system using Wi-Fi technology was developed to provide real-time positioning information. Experimental evaluation with 15 university participants showed excellent acceptance of the multimodal VR feedback, with users naturally adopting spatial reference techniques like wall-following. The localization system was tested across 135 reference points in CEFET buildings, achieving accurate area identification through a hybrid approach combining Euclidean distance methods. Both solutions address the high costs of existing assistive technologies while improving independent mobility for visually impaired people.